“The Amazon Breathes, Dances, and Sings”: : An Analysis of the Rhetorical Use of Personification on the Greenpeace Websites - Honka, Iitu (My University, 2026)
This thesis analyses the rhetorical use of personification in the English-language communication of the eco-activist network Greenpeace. As environmental problems continue to spread, eco-activists are paying increasing attention to the rhetorical strategies through which they can reach wider audiences and get more people involved in their activism. Consequently, it is important to analyse the functionality and application of these rhetorical strategies. The primary focus of this study is to examine both the context in which personification is utilised and the writer’s intended effect behind its usage. The data for this thesis was collected from the News and Stories sections of Greenpeace organisations’ English-language websites. The data is analysed using close reading and the Metaphor Identification Procedure (MIP). Four distinct semantic categories became evident in the research process: personification as metaphors of physical activity, personification as metaphors of emotional activity, personification as metaphors of communicative acts and personification as social role metaphors. These semantic categories represent different uses of personification in Greenpeace’s communication. The results of this study demonstrate that Greenpeace utilises personification as a multifunctional rhetorical strategy, ranging from eliciting emotional responses to establishing connections between human and non-human beings.
Keywords: personification; ecolinguistics; eco-activism; Greenpeace